A Study of University Students’ Public Relations and Recruitment Strategies for ASEAN Opening Community and the 21st Century - Udomtheerakhun, Udomtheerakhun; Bamrungsin, Phanommas; Upamai, Srisalab (11th International Scholars Conference, 2019)
Presently, Thai higher education institutions are more aware of the continual reducing numbers of higher education admission of Thai students which is lower than the provided seats in universities. Hence, the students’ Public Relations and Recruitment Strategies (PRRS) are considered to be the necessary strategies to solve this difficult situation especially in the new challenges of ASEAN opening community and the 21st century era. Therefore, “A study of university students’ PRRS for ASEAN opening community and the 21st century” was conducted. The purposes of this research were to 1) study the important channels of PRRS and 2) provide the effective strategies of PRRS in this era. The survey research was conducted by using the seven main indicators as a tool of research to search the PRRS information on the websites of 27 Thai Autonomous Public Universities (TAPU). The data of each indicator were analyzed in to percentage and ordered them. The findings show that mostly TAPUs provided the important channels of PRRS such as online admission application form, electronic posters, Facebook, call centers, radio, and Youtube. Hence, it was recommended that the Memorandum of Understanding (MoU) strategy should be utilized for this era as well.